Empowering Small Businesses Through Fintech Adoption in Cross Border Payments in Africa - Ali Nuhu Abubakar; Hadiza Nasir Iro; Ummi Hafsat Akawu; Safiyya Shehu Ahmad (Help: Journal of Community Service, 2026)
The rapid growth of digital financial services presents new opportunities for enhancing cross-border trade and financial inclusion in Africa. This study aims to examine how fintech adoption can empower small businesses and improve cross-border payment systems within a community-based service framework. This community service initiative employed a Community-Based Research approach involving 30 participants, including small business actors, policymakers, and fintech practitioners across Nigeria, Ghana, Egypt, Rwanda, and South Africa. The program consisted of participatory training, technical assistance, and continuous mentoring. Data were collected through in-depth interviews, field observations, and participatory evaluation, and analyzed using thematic analysis. The findings indicate that 83% of participants experienced improved transaction efficiency, while 76% reported increased access to financial services. Transaction costs decreased from 9.0% to 3.8% (57.78% reduction), and transaction time improved from 2–5 days to less than 24 hours, with 65% achieving real-time transactions. Additionally, 72% of participants reported increased confidence, and 68% reduced reliance on intermediaries. Challenges remain, including regulatory barriers (73%), limited internet access (60%), and low digital literacy (55%). The study confirms that fintech adoption significantly enhances operational efficiency, financial inclusion, and community empowerment. These findings align with key theoretical frameworks, including financial inclusion theory, transaction cost theory, and diffusion of innovation. However, structural challenges such as regulatory fragmentation and digital inequality must be addressed to ensure long-term sustainability. The study highlights the importance of integrating technological innovation with community-based approaches to achieve inclusive and sustainable economic development.